2015
DOI: 10.1002/adma.201504866
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance Hydrogen Evolution from MoS2(1–x)Px Solid Solution

Abstract: Thermally annealing mixtures of MoS2 and red phosphorus from 1:0.5 to 1:8 w:w ratio at 750 °C for 1 h under argon/hydrogen leads to the formation of a MoS2(1−x)Px solid solution (x = 0 to 1). At x = 0.53, the solid solution possesses one of the highest hydrogen evolution reaction (HER) activities of non-precious-metal-based electrocatalysts. The effective and stable electrocatalyst for hydrogen evolution in acidic solution developed here holds promise for substitution of scarce and expensive platinum. The high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
228
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 325 publications
(240 citation statements)
references
References 29 publications
11
228
0
1
Order By: Relevance
“…From experimental and theoretical calculations, it has been reported that the synchronized active sites possessed by P bonding with transition metal ions relatively enhance the HER catalytic activity. [4a,30] When compared to previous reported works (Figure B, and Table S1 in the Supporting Information) on molybdenum phosphides (MoP/Ti—117 mV[4a]; MoP‐CA2/GC—125 mV; MoP/GC—150 mV[4b]; MoS 0.94 P 0.53 —150 mV; MoP particles—246 mV; MoP/Carbon black—141mV) and chalcogenides (MoS x /N‐CNT—110 mV; MoSSe—164 mV[14b]), our proposed material P/Se‐MoS 2 has thus far revealed a much lower catalytic overpotential of 93 mV. In addition, to demonstrate the HER activity in neutral (pH = 7) and alkaline (pH = 14) medium, experiments were carried out with the same operating parameters as followed in acidic medium (discussion with respect to pH variant and corresponding polarization curves were detailed in Figure S5, Supporting Information).…”
Section: Resultsmentioning
confidence: 85%
“…From experimental and theoretical calculations, it has been reported that the synchronized active sites possessed by P bonding with transition metal ions relatively enhance the HER catalytic activity. [4a,30] When compared to previous reported works (Figure B, and Table S1 in the Supporting Information) on molybdenum phosphides (MoP/Ti—117 mV[4a]; MoP‐CA2/GC—125 mV; MoP/GC—150 mV[4b]; MoS 0.94 P 0.53 —150 mV; MoP particles—246 mV; MoP/Carbon black—141mV) and chalcogenides (MoS x /N‐CNT—110 mV; MoSSe—164 mV[14b]), our proposed material P/Se‐MoS 2 has thus far revealed a much lower catalytic overpotential of 93 mV. In addition, to demonstrate the HER activity in neutral (pH = 7) and alkaline (pH = 14) medium, experiments were carried out with the same operating parameters as followed in acidic medium (discussion with respect to pH variant and corresponding polarization curves were detailed in Figure S5, Supporting Information).…”
Section: Resultsmentioning
confidence: 85%
“…Another efficient way to enhance the HER performance of MoS2 is to form MoS2-based alloys [69][70][71][72][73]. Our group synthesized monolayer MoS2(1−x)Se2x alloys and MoS2(1−x)Se2x nanobelt alloys via a CVD method by using MoO3, S powder, and Se powder as reactants [69,73].…”
Section: Catalytic Performance In Alloy Structuresmentioning
confidence: 99%
“…For example, Tour et al, reported that, by annealing particulate MoS 2 with different amounts of red phosphorus at ≈750 °C in argon/hydrogen flow, MoS 2 gradually transformed into MoS 2(1-x) P x with x varying from 0 to 1. [147] A synergistic effect of alloyed MoS 2 and MoP was observed in subsequent HER measurements, showing an optimal performance at x = 0.53. An overpotential of only ≈150 mV was needed to deliver a current density of 10 mA cm −2 (Figure 11d).…”
Section: Advanced Electrocatalysts For Hydrogen Evolution Reactionmentioning
confidence: 81%
“…[147] Reproduced with permission. [147] Copyright 2016, Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim. e) Schematic process for producing MoS 2 /RGO hybrids.…”
Section: Advanced Electrocatalysts For Hydrogen Evolution Reactionmentioning
confidence: 99%
See 1 more Smart Citation